Preconditioning boosts regenerative programmes in the adult zebrafish heart - Anne-Sophie de Preux Charles (Open Biology, 2016)
During preconditioning, exposure to a non-lethal harmful stimulus triggers a body-wide increase of survival and pro-regenerative programmes that enable the organism to better withstand the deleterious effects of subsequent injuries. This phenomenon has first been described in the mammalian heart, where it leads to a reduction of infarct size and limits the dysfunction of the injured organ. Despite its important clinical outcome, the actual mechanisms underlying preconditioning-induced cardioprotection remain unclear. Here, we describe two independent models of cardiac preconditioning in the adult zebrafish. As noxious stimuli, we used either a thoracotomy procedure or an induction of sterile inflammation by intraperitoneal injection of immunogenic particles. Similar to mammalian preconditioning, the zebrafish heart displayed increased expression of cardioprotective genes in response to these stimuli. As zebrafish cardiomyocytes have an endogenous proliferative capacity, preconditioning further elevated the re-entry into the cell cycle in the intact heart. This enhanced cycling activity led to a long-term modification of the myocardium architecture. Importantly, the protected phenotype brought beneficial effects for heart regeneration within one week after cryoinjury, such as a more effective cell-cycle reentry, enhanced reactivation of embryonic gene expression at the injury border, and improved cell survival shortly after injury. This study reveals that exposure to antecedent stimuli induces adaptive responses that render the fish more efficient in the activation of the regenerative programmes following heart damage. Our results open a new field of research by providing the adult zebrafish as a model system to study remote cardiac preconditioning.